(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the influence of Information and Communication Technology (ICT) on job satisfaction among school teachers. With the increasing push for digital literacy and e-learning integration in rural and semi-urban education systems, it is crucial to examine how ICT adoption affects teachers’ motivation, teaching experience, and overall job satisfaction.